PENGGUNAAN MEDIA PAPAN CATUR MANIPULATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI.MIPA.1 - Risnita Risnita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
This research starts from the low results of learning mathematics students. This can be seen in the daily test of students who are below the Minimum Completion Criteria (MCC). One reason is a low understanding of mathematical concepts. Low understanding of concepts is due to the fact that mathematics is still abstracted by students. Abstract mathematical concepts for students will be easily understood if learning uses learning media. Learning carried out is discovery learning using manipulative chessboard media. This study aims to determine the improvement in learning outcomes of students of class XI MIPA 1 SMAN 1 Pangkalan Kerinci and conducted in two cycles consisting of planning, action, observation and reflection. The research data collected is data on learning outcomes and field notes. The collected data was analyzed descriptively. The results of this study indicate that the use of manipulate chess shooting media with discovery learning methods can improve learning outcomes. The learning outcomes of students from the first cycle and second cycle increased by 36.11%. Based on the research findings, it can be concluded that the use of manipulate chess shooting media with guided methods can improve learning outcomes on the subject of geometric transformation.